Raman and Surface Enhanced Raman Signals of the Sensor 1-(4-Mercaptophenyl)-2,4,6-Triphenylpyridinium Perchlorate - Aliaga-Vidal, C; Aliaga-Vidal, C (Sociedad Chilena de Quimica, 2015)
The sensor 1-(4-mercaptophenyl)-2,4,6-triphenylpyridinium perchlorate compound was vibrationally characterized using Raman and the Surface-Enhanced Raman techniques, SERS and Shell-Isolated Nanoparticles-Enhanced Raman Spectroscopy (SHINERS). The Raman spectrum was analyzed and the band assignment was supported using DFT data at the B3LYP/6-31G(d) level. SERS data allowed infer about the orientation of the analyte on the naked Ag surface. EHT calculations for an Ag/analyte model represent well the SERS spectrum supporting the Ag-S bond formation. The SHINERS spectrum was obtained by using Ag@SiO2 nanoparticles prepared at two different time of the SiO2 coating process. The most intense SHINERS spectral signals of the compound (100 nM) were obtained after 20 minutes of the Ag@SiO2 formation. No charge-transfer was concluded from the SHINERS experiments.